2020
DOI: 10.1097/nna.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Adverse Effects of 12-Hour Shifts

Abstract: OBJECTIVE The purpose of this study was to explore perspectives of nurse leaders regarding strategies to mitigate the job demands of 12-hour shift work and learn their views regarding the role of breaks in offsetting the cognitive and physical demands of acute care nurses working 12-hour shifts. BACKGROUND The strain of long shifts can result in adverse outcomes for nurses, organizations, and patients. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Sufficient days off between long shifts, regular breaks during the shift and working with familiar patients may mitigate some of the negative impacts on 12-h shifts (Harris et al. , 2015; Keys, 2020; Ejebu et al. , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient days off between long shifts, regular breaks during the shift and working with familiar patients may mitigate some of the negative impacts on 12-h shifts (Harris et al. , 2015; Keys, 2020; Ejebu et al. , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Introducing full-time culture with long shift implies less vacancy in the rotation schemes, which will give more continuity and predictability for both patients and staff. Some studies suggest that healthcare personnel need to slow down the pace during long shifts to maintain enough energy until the end of the shift (Keys, 2020). This seems to apply especially to older employees than the younger ones.…”
Section: Discussionmentioning
confidence: 99%
“…The organization’s staffing procedures should be evaluated as part of the organization’s quality improvement program through analysis of nursing outcomes relative to perioperative staffing patterns 1,2,13 Other implications for staffing and on‐call plans include planning for ○responding to fatigue that occurs among professionals – it is important to have a plan to mitigate fatigue‐related risks for the perioperative team and patients (ie, have a fatigue management plan, provide uninterrupted breaks from continuous duty); 1,14‐21 ○urgent and emergent patient needs during the organization’s defined hours of operation (eg, added on cases, 24 hours 7 days per week); ○relief for personnel when patient care needs extend beyond the scheduled staff hours; ○how to determine direct and indirect caregivers required in the specific setting; ○budgeting and operationalizing both productive (ie, direct patient care) and nonproductive (ie, PTO, participation in organizational committees, self‐governance, maintenance of preference cards, and other activities required for safe, efficient management of patient care within the department) time; and ○excluding orientees from staffing allocation until he or she has completed orientation and is identified as professionally competent to work independently 22 On‐call staffing plans should ○support perioperative teams to recognize fatigue as a risk to patient and employee safety rather than a sign of a worker’s dedication to the job 2 …”
Section: Position Statementmentioning
confidence: 99%
“…10 Respite and breaks are critical to recovery from stress for nurses and other healthcare workers. 11,12 Conversely, Sagherian and colleagues found that nurses and unlicensed assistive personnel who skipped breaks scored significantly higher on measures of posttraumatic stress disorder. 13 Several studies involving interventions to increase resilience demonstrated promising results, but there's no commonly endorsed approach to reducing burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Kometiani stressed the importance of workplace wellness addressing emotional and psychological health along with workers' physical health 10. Respite and breaks are critical to recovery from stress for nurses and other healthcare workers 11,12. Conversely, Sagherian and colleagues found that nurses and unlicensed assistive personnel who skipped breaks scored significantly higher on measures of posttraumatic stress disorder 13…”
Section: Introductionmentioning
confidence: 99%